Gender-specific correlations between remnant cholesterol and severe abdominal aortic calcification in American adults - Yan, Laisha; Hu, Xiaoyan; Wu, Shanshan; Zhao, Shunying (Frontiers in Endocrinology, 2024)
Background Remnant cholesterol (RC) predicts cardiovascular risk and is associated with a range of diseases, including asthma, hypertension, depression, periodontitis, and alcoholic fatty liver disease. However, its correlation with abdominal aortic calcification (AAC) has not been reported. Methods Using a cross-sectional approach, this study examined data from the 2013-2014 National Health and Nutrition Examination Survey (NHANES) cycle. Multiple logistic regression, generalized summation models, and subgroup analyses were used in examining the correlation between RC and the prevalence of severe AAC. Results The mean age of participants in this study was 57.70 ± 11.73 years, with 142 individuals (9.67%) suffering from severe AAC. The median RC was 0.52 mmol/L (Q1-Q3, 0.36-0.75 mmol/L). Among female participants, a significant positive correlation was observed between RC and severe AAC (per natural log [RC] increment: 2.14; 95% CI, 1.07-4.27). Smooth curve fitting and threshold effect analysis revealed a saturation effect at an RC level of 0.57 mmol/L. Conversely, in male participants, no significant correlation was found between RC and the prevalence of severe AAC (per natural log [RC] increment: 0.88; 95% CI, 0.43-1.78). Our findings suggest a significant interaction between gender and RC in relation to severe AAC (P for interaction = 0.0042). Conclusions Higher RC levels were significantly associated with an increased prevalence of severe AAC in women.